2008
DOI: 10.1016/j.bcp.2008.09.007
|View full text |Cite
|
Sign up to set email alerts
|

c-FLIP knockdown induces ligand-independent DR5-, FADD-, caspase-8-, and caspase-9-dependent apoptosis in breast cancer cells

Abstract: Cellular-FLICE inhibitory protein (c-FLIP) is an inhibitor of apoptosis downstream of the death receptors Fas, DR4, and DR5, and is expressed as long (c-FLIP L ) and short (c-FLIP S ) splice forms. We found that the knockdown of c-FLIP using small interfering RNA (siRNA) triggered ligandindependent caspase-8-and -9-dependent spontaneous apoptosis and decreased the proliferation of MCF-7 breast cancer cells. Further analysis revealed that an apoptotic inhibitory complex (AIC) comprised of DR5, FADD, caspase-8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 62 publications
7
66
1
Order By: Relevance
“…Furthermore, Day and colleagues reported that c-FLIP knockdown induced ligand-independent and DR5-dependent apoptosis in breast cancer cells (13). In this study, we showed that the combined treatment with OBP-801 and celecoxib stimulated the binding of pro-caspase-8 to DR5 in T24 bladder cancer cells (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, Day and colleagues reported that c-FLIP knockdown induced ligand-independent and DR5-dependent apoptosis in breast cancer cells (13). In this study, we showed that the combined treatment with OBP-801 and celecoxib stimulated the binding of pro-caspase-8 to DR5 in T24 bladder cancer cells (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 58%
“…2B and C, the cotreatment upregulated the expression of DR5 and downregulated the expression of FLIP L . Day and colleagues reported that c-FLIP L interacts with DR5 and caspase-8 to form an apoptotic inhibitory complex that inhibits spontaneous DISC signaling (13). Therefore, we next examined whether the cotreatment encouraged DISC signaling.…”
Section: Dr5 Is Involved In Apoptosis By the Cotreatment With Obp-801mentioning
confidence: 97%
“…This speculation is further supported by the finding that knockdown of FADD, which is a crucial adaptor for recruiting caspase-8 into DISC and its subsequent activation, resulted in a similar degree of inhibition of PS1-induced apoptosis. This observation is in agreement with previous studies that show that FADD is required for c-FLIP knockdown-triggered caspase-8 activation and apoptosis (38,40).…”
Section: Discussionsupporting
confidence: 94%
“…35 and 36). Many previous studies have shown that knockdown or downregulation of c-FLIP results in ligand-independent, but caspase-8-dependent, spontaneous apoptosis (37)(38)(39). Thus, our observation that ␄-secretase inhibitor, which inhibited the turnover of both c-FLIP L and c-FLIP S , also partially blocked PS1-induced apoptosis strongly suggests that PS1-induced apoptosis is at least partially mediated by ␄-secretase-catalyzed turnover of c-FLIP.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, we found that both c-FLIP L and c-FLIP S are degraded independently of proteasomal function by either a viral protease or a virus-induced cellular protease, excluding inhibition of translation by RNA interference as an underlying mechanism. In contrast, proteasome-dependent degradation of c-FLIP has been observed in other situations, including activa- pathway, as shown recently for breast cancer cells (14). In accordance with this view, death ligands, including CD95, TRAIL receptor, and tumor necrosis factor (TNF) receptor, contributed weakly and only in some donors to apoptosis of HSV-1-infected iDCs (44).…”
Section: Discussionmentioning
confidence: 52%